Radiation dynamics on crop productivity in different cropping systems - I., Nur Arina; M. Y., Martini; S., Surdiana; R., Mohd Fauzi; S., Zulkefly (Hindawi Limited, 2021)
Global demand for food has always been on the increase due to the increase of the population in this world. Intercropping is one of the alternatives of agronomic practices that is widely practiced in ensuring food security and enhancing yield stability. Strip, mixed, and relay intercropping can be practiced to increase crop production. In addition to achieving a successful intercropping system, factors such as suitable crops, time of sowing, maturity of the crop, and plant density need to be considered before and during planting. Besides, practiced intercropping becomes a useful cropping system to increase efficient resource utilization, enhance biodiversity, promote soil health, enhance soil fertility, erosion control, yield advantage, weed, pest, and disease control, insurance against crop failure, ecosystem and modification of microclimate, market instability, and increase farmers income. Crop productivity in any types of cropping system implemented relies primarily on the interception of photosynthetically active radiation (PAR) of crop canopy and conversion of intercepted radiation into biomass or known as radiation use efficiency (RUE). Both PAR and RUE are important measurements that have significant roles in crop growth and development in which the accessibility of these radiation dynamics is connected with the leaf area index and crop canopy characteristics in maximizing yield as well as total productivity of the crop component in intercropping systems.